Identification and Validation of Genomic Subtypes and a Prognostic Model Based on Antigen-Presenting Cells and Tumor Microenvironment Infiltration Characteristics in Hepatocellular Carcinoma - Chen, Ji; Li, Chunxue; Lang, Zhichao; Zheng, Jianjian; Yu, Suhui; Zhou, Zhenxu (Frontiers in Oncology, 2022)
Currently, the prognosis of hepatocellular carcinoma (HCC) is poor and there is a lack of effective targeted therapy. As key mediators of the immune response, the prognostic value of antigen-presenting cells (APCs) in HCC still remains unclear. In this study, we aimed to identify APCs-related genomic subtypes and develop a novel prognostic model in HCC. Our results indicated that overall survival (OS) and the level of immune infiltration significantly differed between different APCs clusters. By analyzing the gene expression profile between APCs clusters, APCs-related genomic subtypes were identified. There was a significant difference in OS and tumor microenvironment infiltration in HCC patients with different genomic subtypes. With the aid of genomic subtypes, significantly differentially expressed genes were screened to generate a novel prognostic model. The risk score of the model had a significant positive correlation with APCs and was associated with immune checkpoint expressions. Through the clinical cohort collected from the First Affiliated Hospital of Wenzhou Medical University, the prognostic value of the risk score was further validated (Hazard Ratio (HR), 1.300; 95% confidence interval (CI), 1.128-1.497; p < 0.001). Moreover, after combining the risk score and clinical characteristics, a nomogram was constructed to evaluate the prognosis for HCC patients. In conclusion, we mainly identified the APCs-related genomic subtypes and generated a novel prognostic model to improve the prognosis prediction and targeted therapy for HCC patients.